Gestão democrática da escola pública : o jogo para além das regras - Scalabrin, Ionara Soveral (2012)
Democratic administration of public education is by law a right granted by the Brazilian Federal Constitution of 1988. The present thesis conceptualizes, characterizes, and analyzes the democratic administration of public schools in its interface with the right to education, the perspective to promote thoughts and practices based on participation and autonomy of the educational community. Moreover, through literature research, it seeks to discuss what are the principles that found the democratization of public school administration? The goal is to constitute thinking and critical reference of the practice itself, and also as analysis instrument to support policies and practices of public schools, which look for the democratization of administration. The first chapter conceptualizes, characterizes, and historicizes democracy; it presents the rules of the democratic game in representative democracy ; and discusses it from the proposal of democratization , affirming it as a process of continuous work by spreading the political field through direct participation of citizens. The second chapter talks about the fundamental right to quality public schools; it analyzes indicators regarding the accomplishment of this right; and it identifies the democratization of accessing public schools as a game beyond what is established by human rights. The third chapter conceptualizes education administration and school democratic administration, characterizing and historicizing them; it presents democratic administration as an assured and existent right in Brazil; it analyzes its accomplishment within the rule of the game of participative democracy, concerning the elections for school principal; it states that there are different forms of accomplishing ( different games ) the principle of school democratic administration ( the same rule ), which is in political dispute; it discusses the centrality assumed by schools in the processes of educational administration and its relation to the educational system; and it reflects on the social role of school in front of different administration paradigms and pedagogical trends. The fourth chapter discusses the relative autonomy of school facing the educational system as a required element to the outbreak of forms of direct democracy in school administration ( the game beyond the rules ); it conceptualizes participation; and it presents some of its constraints and possible ways of applying it in school administration. The main findings of the research are: (i) the democratization of schools permeates the democratization of administration, the democratization of access to education, and democratization in the definition of purposes and objectives of schools and education; (ii) the achievement of (relative) autonomy of school, through direct and active participation of its members, becomes a formative practice ; and (iii) participation is the main form of democratization of school administration, with the ability and duty to be stimulated, for it is not something natural, or easy, or that can be given . The investigation stresses the theory that school education should have, as a main goal, the emancipation of individuals, which also depends on the experience of democratic school administration